Antioxidative and Lipid Lowering Effects of 7,8-Dihydroxy-3-(4-methylphenyl) Coumarin in Hyperlipidemic Rats - (:unkn) unknown (GEORG THIEME VERLAG KG, 2009)
In this study, 7,8-dihydroxy-3-(4-methylphenyl) coumarin (DHMPC), a new coumarin derivative, was tested for the first time to determine whether it had any antioxidant and lipid lowering effects. Hypercholesterolernia was induced by feeding rats with a high cholesterol diet for 17 days. The lipid lowering and antioxidant effects of DHMPC were compared with those of hesperidin (CAS 520-26-3) and rutin (CAS 153-18-4), which have been pharmacologically determined as potential lipid lowering and antioxidant agents. DHMPC significantly decreased serum total cholesterol levels but not as efficient as hesperidin. When the ratios of high density lipoprotein-cholesterol (HDL-cholesterol) to total cholesterol were evaluated, the most significant changes were observed in DHMPC and rutin treatments. The results of serum triglyceride levels indicate that DHMPC and hesperidin did not significantly decrease triglyceride level when compared to rutin group but prevented it to rise. Serum malondialdehyde (MDA) levels increased as expected in high cholesterol diet groups but no significant decrease was observed for serum MDA levels in all treated groups. In contrast to serum MDA levels, liver homogenates MDA levels decreased in all treated groups but a considerable decrease was not observed for DHMPC treated group. Liver homogenates glutathione (GSH) levels drastically decreased in hyperlipidemic group and increased in all treated groups. As a conclusion DHMPC displayed both antioxidant and lipid lowering effects and can be a candidate drug for further studies.
Keywords: Antioxidants; CAS 153-18-4; CAS 520-26-3; Coumarin derivatives; 7,8-Dihydroxy-3-(4-methylphenyl) coumarin; Flavonoids; Hesperidin; Lipid lowering agents; Rutin; RUTIN; HESPERIDIN; FLAVONOIDS; QUERCETIN; ACID